Charged Particles (IntechOpen, 2023)
A charged particle is a particle that carries an electric charge and can be discussed in many aspects. This book focuses on cutting-edge and important research topics such as flavor physics to search for new physics via charged particles that appear in different extensions of the standard model, as well as the analysis of ultra-high energy muons using the pair-meter technique. Also included in this book are the idea of the Eloisatron to PeVatron, the important research field of electrostatic waves in magnetized electron/positron plasmas, and the application of charge bodies.